Phytochemical analysis and biogenic synthesis of silver nanoparticles from Phlomis bracteosa Royle ex Benth. and screening of their antimicrobial and antioxidant potential - Jagriti Rana; Ankush Sharma; Jyoti Rana; Anand Sagar (Micro and Nano Systems Letters)
Abstract The Phlomis bracteosa Royle ex Benth. is one of the medicinal plants used by the people of the north-western Himalayan region, India. Initially, phytochemical components of this plants have been evaluated by estimating total phenolic, flavonoid and tannin contents, and also by GCMS analysis in acetone and methanol solvents, which listed twenty-four compounds in acetone and twenty-two in methanol extract with different percentage peak areas. Later, silver nanoparticles (SNPs) were biogenically synthesized from the acetone extract of the same plant. The formation of SNPs was observed with UV-vis spectroscopy with surface plasmon resonance (SPR) at 438 nm. Further, the Fourier transform infrared spectroscopy suggested the presence of carbonyls, nitrogenous compounds and different types of hydrocarbons in SNPs. The field emission scanning electron microscopy (FESEM) and the high-resolution transmission electron microscopy suggested the spherical shape of SNPs with average size of 43.53 ± 0.71 nm. On the other hand, the energy dispersive X-ray spectroscopy depicted Ag as major element, the selected area electron diffraction and the X-ray diffraction supported crystalline nature of synthesized SNPs. The antimicrobial and antioxidant activities of both extracts (acetone and methanol) and SNPs were also studied. For the antimicrobial activity analysis, disk diffusion and broth microdilution methods were selected which displayed that plant extracts (PEs) exhibited better activity against Gram-positive bacteria and were inactive against Escherichia coli, while synthesized SNPs displayed better antimicrobial activity against all selected microorganisms. In case of antioxidant activity, by following two methods i.e., DPPH radicle scavenging and reducing power methods again SNPs expressed better antioxidant property with lower IC50 value (40.55 µg/mL) than PEs i.e., 93.48 µg/mL (acetone) and 92.57 µg/mL (methanol). Therefore, biosynthetic SNPs can be a useful strategy in the biomedical sector.